Confirmation of the Recognition of Indigenous Peoples in Indonesia - Siti Khoiriah; Candra Perbawati (Utan Kayu Publishing, 2026)
Indigenous people and individuals enjoy freedom and equality with other communities and individuals, the right to bee free from all discrimination, the right to self-identification, civil and political right, economic, social and cultur rights to freedom. In terms of protection customary law communities, it is not only the responsibility of the state but also the UN. However, this only protects the human rights of indigenous peoples, and does not help preserve them. On equality with other communities, cumtomary law communities have their human rights protected, so that their customary rights are also protected. The state must also prepare cumtomary law communities to face changing times so that they are not disturbed by changes and easily accept changes in their modern lifestyle patterns. Efforts to ensure consistent indigenous peopoles protection to overcome these various gaps are based on pure and consistent application of legal principles and provisions contained in statutory regulations and implementing them. Verious conflict phenomena that occur can be caused by the government’s failure to understand and implement the procedures and provisions determined by ststutory regulations.